ChemInform Abstract: Bioinspired Magnetite Synthesis via Solid Precursor Phases. Issue 41 (September 2016) - Lenders, Jos J. M.; Mirabello, Giulia; Sommerdijk, Nico A. J. M.
Abstract: Review: 106 refs.